PERKEMBANGAN PENGATURAN HALAL MENERUSI AKTA PERIHAL DAGANGAN 2011 DI MALAYSIA: The Development of Regulations Concerning Halal through Trade Description Act 2011 in Malaysia - Zakaria, Zalina; Ismail, Siti Zubaidah (Jurnal Syariah, 2015)
The growing market and demand for halal products have created a question of whether the legal structure is adequate to cater for the development of halal industry. Eventhough the Malaysian government has prepared a healthy business infrastructure in order to enhance the positioning of the country as the main halal hub in the world, it does not mean that we are ahead of our counterparts in terms of regulations. The objective of this article is to examine the inadequacy of Trade Description Act 1972 to address the issue of halal and how the amendment made by Trade Description Act 2011 has strengthened many halal aspects. In collecting data, apart from reviewing the Act, interviews were conducted to complement the data. The article found that the amendment made by Trade Description Act 2011 has strengthened the aspects of enforcement, supervision and monitoring of halal logo as well as prosecution of related offences.